Modelo de resfriamento de Newton: uma aplicação de equações diferenciais ordinárias de primeira ordem - Furtado, Thiago Rodrigues (Universidade Federal do Tocantins, 2023)
This work presents the study of a mathematical model known as Newton’s Cooling Model. As it is an application of Differential Equations in Physics, we carried out a bibliographical and exploratory research in these areas for a better understanding and mastery of the object of study. The main objective of this work is to analyze the theoretical data obtained from the calculations produced according to Newton’s Law of Cooling and compare them with the experimental data performed during the research.